The intersection of TB and health financing: defining needs and opportunities - W.A. Wells; S. Waseem; S. Scheening (IJTLD Open)
TB is an airborne public health threat, so the reponse to TB has been defined mainly through the lens of vertical, public-sector national TB programs (NTPs). However, TB exists within a broader health systems and health financing context. Here, we examine the intersection between the particular needs of TB programs and the broader health financing landscape. This includes the strategies needed to finance both the clinical and public health aspects of the TB response. In high-burden countries, the resource mobilization and strategic purchasing approaches described here will be critical if we are to maximize the reach and impact of the TB response.